Feasibility Verification of Mountable PZT-Interface for Impedance Monitoring in Tendon-Anchorage - Thanh-Canh Huynh; Young-Hwan Park; Jae-Hyung Park; Jeong-Tae Kim (Shock and Vibration)
This study has been motivated to numerically evaluate the performance of the mountable PZT-interface for impedance monitoring in tendon-anchorage. Firstly, electromechanical impedance monitoring and feature classification methods are outlined. Secondly, a structural model of tendon-anchorage subsystem with mountable PZT-interface is designed for impedance monitoring. Finally, the feasibility of the mountable PZT-interface is numerically examined. A finite element (FE) model is designed for the lab-scaled tendon-anchorage. The FE model of the PZT-interface is tuned as its impedance signatures meet the experimental test results at the same frequency ranges and also with identical patterns. Equivalent model properties of the FE model corresponding to prestress forces inflicted on the lab-tested structure are identified from the fine-tuning practice.